Architectural character: Exploring form and construction - Ek, Elisabeth (My University, 2022)
This thesis seeks to investigate ways to explore and convey character in architecture. Through an exploration of how character relates to form and construction, it aims for craftmanship and a sense of playfulness. Qualities in a selection of existing buildings are studied to create a vocabulary for inspiration. This makes a starting point for the design work that is implemented in a program of atelier houses, where characteristic and playful qualities are tested. This project is a reaction to the generic building industry, generally lacking the qualities mentioned above. I have a longing for buildings that contrast the anonymous and standardized. The vernacular architecture is often intriguing where there are irregular lines, tactility, and a human scale. Two main references are studied: Japanese architect Terunobu Fujimori and vernacular architecture of Gotland, Sweden. They corelate as they are both non- normative, where Fujimori is a contemporary practitioner that uses natural materials, embraces work made by hand and makes architecture with a sense of playfulness. This is shared with the vernacular architecture of Gotland, which also holds a traditional craftmanship knowledge in the construction. They are differentiated by time and by geography, yet Fujimori is often inspired by vernacular architecture. The leading question for the thesis is: Which approaches to design regarding character can be conceived whilst making a synthesis of the works of Terunobu Fujimori and the Gotlandic vernacular architecture? This thesis embraces the research through design- approach and focuses on methods of physical models built by hand. The models are iterated into digital drawings, alternating between the two mediums. The materials in focus are primarily wood and reed, followed by clay and stone. There seems to be a longing for alternative ways to build and a revival for craft, contrasting the industrial and abstract aspects of today’s society. The character of the natural materials could not only hold tactical qualities but also sustainable ones. Designing with the aim of craftmanship is, to me, to show care for the users, and it often shows marks of the creators.
Keywords: Character; Craftmanship; Vernacular; Gotland; Terunobu Fujimori